(untitled) (Tempo e Argumento, 2013)
Gaston Bergery wasborn in 1892 and died in 1974. He was a lawyer and a French politician. From editor of the political magazineLa Flèche, he became the ambassador in Turkey during the Vichy government. We aim to,through the analysis of letters, articles and other personal and public documents, trace the trajectory of this individual, who was politically active during the first half of the twentieth century. To this, we have made anextensive research through several files, including that of the Castle of Vincennes (the Army file), the Quais d’Orsay (the Ministry of Foreign Affairs files), the National Archives, the Hoover Foundation, Yale University, as well as some oral interviews.